MUSCLE DAMAGE AFTER A TENNIS MATCH IN YOUNG PLAYERS - Gomes, R.V.; Santos, R.C.O.; Nosaka, K.; Moreira, A.; Miyabara, E.H.; Aoki, M.S. (Biology of Sport, 2014)
The present study investigated changes in indirect markers of muscle damage following a simulated tennis match play using nationally ranked young (17.6 ± 1.4 years) male tennis players. Ten young athletes played a 3-hour simulated match play on outdoor red clay courts following the International Tennis Federation rules. Muscle soreness, plasma creatine kinase activity (CK), serum myoglobin concentration (Mb), one repetition maximum (1RM) squat strength, and squat jump (SJ) and counter movement jump (CMJ) heights were assessed before, immediately after, and 24 and 48 h after the simulated match play. All parameters were also evaluated in a non-exercised group (control group). A small increase in the indirect markers of muscle damage (muscle soreness, CK and Mb) was detected at 24-48 hours post-match (p<0.05). A marked acute decrement in neuromuscular performance (1RM squat strength: -35.2 ± 10.4%, SJ: -7.0 ± 6.0%, CMJ: -10.0 ± 6.3%) was observed immediately post-match (p<0.05). At 24 h post-match, the 1RM strength and jump heights were not significantly different from the baseline values. However, several players showed a decrease of these measures at 24 h after the match play. The simulated tennis match play induced mild muscle damage in young players. Coaches could monitor changes in the indirect markers of muscle damage to assess athletes’ recovery status during training and competition.